Bitumen rheology and the impact of rejuvenators. (20th October 2019) - Ganter, Domenic; Mielke, Tommy; Maier, Marc; Lupascu, Doru C.
Highlights: Surface microstructure of bitumen is not directly connected with the bulk viscosity. Surface structure changes due to the binders' chemistry. Rejuvenators have huge influence on the bulk viscosity. Rejuvenators change the microstructure of the bitumen surface. Abstract: Bitumen is a material used in many industrial applications. It is the primary binding material for road pavements in asphalt. To improve sustainability, it is important to be aware of the finite nature of conventional oil reserves. As a cost and energy saving material, reclaimed asphalt pavement can help preserve our resources. Virgin binder ages significantly during its service life time yielding declining mechanical properties. As material properties of bitumen are responsible for the endurance of asphalt pavements, adding rejuvenators is supposed to restore the mechanical properties like the original bitumen properties. In this paper, three different rejuvenators were studied using one common polymer modified bitumen PmB 25/55-55 A. The virgin binder was aged in two different aging steps (short and long-term) and rheological properties were determined by traditional bitumen tests and dynamic shear rheometer (DSR) tests. For a better understanding of rejuvenation on the microscale, virgin, aged, and modified bitumen samples were measured using Optical Microscopy and Atomic Force Microscopy (AFM). Aging has significant influence on the macro- and micro-Rheology of bitumen. It causes changes in viscosity and at the same time clear changes in its surface structure. All Rejuvenators positively influence the rheological properties to different extents. Atomic Force Microscopy revealed considerable changes of the morphology between virgin, aged, and rejuvenated binders. The combination of rheological properties and micro structure imaging is an important tool in advancing and optimizing reclaimed asphalt pavement.